2016
DOI: 10.1515/cdbme-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on 3D printing of barium titanate ceramics for medical applications

Abstract: Abstract:The present work deals with the 3D printing of porous barium titanate ceramics. Barium titanate is a biocompatible material with piezoelectric properties. Due to insufficient flowability of the starting material for 3D printing, the barium titanate raw material has been modified in three different ways. Firstly, barium titanate powder has been calcined. Secondly, flow additives have been added to the powder. And thirdly, flow additives have been added to the calcined powder. Finally, a polymer has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…After sintering, the largest contraction was observed in the case of the M1 sample, of 75.53%, but the other two also recorded relatively high contractions, M2 of 40.55% and M3 of 29.51%. The results reported in their study confirm that porous barium titanate ceramics can be used as a 3D structure for bone tissue engineering and bone formation can be promoted by electrical stimulation [25].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…After sintering, the largest contraction was observed in the case of the M1 sample, of 75.53%, but the other two also recorded relatively high contractions, M2 of 40.55% and M3 of 29.51%. The results reported in their study confirm that porous barium titanate ceramics can be used as a 3D structure for bone tissue engineering and bone formation can be promoted by electrical stimulation [25].…”
Section: Introductionsupporting
confidence: 54%
“…Regarding 3D printing of barium titanate (BT) ceramics for medical applications, Schult et al [25], have shown that BT powder can serve as a material for bone reconstruction, obtained by 3D printing cylindrical parts with 11.7 mm in diameter and 3.51 mm high, out of the three BT-based mixtures. The first mixture, M1, consisted of untreated BT powder, a stable polymer, and a flow additive-AEROSIL R8200.…”
Section: Introductionmentioning
confidence: 99%
“…3D printed BT [237][238][239], modified KNN [240], PVDF [241,242] and PLLA [243] have recently been fabricated for piezoelectric sensors and functional scaffolds which have limitedly been researched for tissue engineering applications. There are however challenges in processing and formulation of the raw material for printing and inducing piezoelectricity.…”
Section: D Printing Of Piezoelectric Materialsmentioning
confidence: 99%
“…printed cylindrical green parts (11.7 mm diameter and 3.51 mm height) for making BT scaffolds [238]. It was observed that the green bodies formed were unstable and sintering lead to substantial shrinkage.…”
Section: D Printing Of Piezoelectric Materialsmentioning
confidence: 99%
“…In the following study, a composition containing 68 wt.% BaTiO 3 , 18 wt.% HA and 14 wt.% PEMA, featuring high flowability crucial for powder-based printing was used [23]. The resulting material mixture will be called BaTiO 3 /HA composite.…”
Section: Fabricationmentioning
confidence: 99%